POSTOPERATIVE RECOVERY OF THE METACARPAL V FRACTURE BY USING KINESIOTHERAPY RESOURCES (GYMNASIUM, 2017)
The problem of traumas that occur at hand level isone of continuing importance because of thelarge and constant number of cases that require medication, from the easiest to the more complex (surgery). This study intends to demonstrate and show the importance of kinesiotherapy and hydro-kinesiology program in the process of the recovery of the metacarpal V fracture. The means used by kinesiotherapy and hydro-kinesiotherapy are capable to reduce and eliminate the symptoms and aftermath of fractures.The initial and final evaluation represent imperative components in the implementation of a recovery plan. Kinesiotherapy and hydro-kinesiotherapy can restore the normal functions of the disabled member.